MONOPOLIZATION OF INFORMATION TECHNOLOGY AND THE WEAKENING OF DEMOCRACY: ANALYSIS OF THE NATIONAL AND INTERNATIONAL POLITICAL SCENARIO IN THE FACE OF "ALGORITARIANISM" (REMUNOM, 2025)
This article offers a critical analysis of the growing concentration of power of Big Techs, through the extensive and massive collection of user data and subsequent strategic use or sale of this data. To contextualize the situation, the article discusses the democratic evolution of Brazil - crucial to understanding the fundamental rights resulting from a democracy - and the evolution of authoritarian governments. It also addresses the recent rise of Big Techs, “algoritarianism”, the resulting democratic crises, as well as emblematic cases of the use of data collected from social media users for electoral manipulation. In the final analysis, it is concluded that the dominance of Big Techs not only weakens democratic institutions and citizens' trust in the electoral system, but also establishes a new “digital coronelismo”, where data is used as a bargaining chip to influence political behavior. It calls for the immediate need for regulations that reestablish the balance between freedom of expression, data protection and corporate responsibility, in order to protect democratic sovereignty against the hegemony of digital platforms.